GEODIVERSITY OF GRÃO MOGOL STATE PARK, MINAS GERAIS - Aguiar, Patrícia Rosa (2024)
In the conservation units there are examples of geosites with didactic potential for disseminating and understanding concepts linked to the functioning of planet Earth, its influence on the existence, variety and distribution of life forms and how humanity fits into this context. The general objective of this research is to analyze the scientific, didactic and tourist potential of the Grão Mogol State Park conservation unit and its surroundings (city). To this end, bibliographical research was used, maps were created using the ArcGis 10.3 software and the geodiversity of the park was evaluated in a qualitative and quantitative way, based on scientific, didactic and tourist values, in addition to its risk of degradation. Despite the difference in scores, the evaluation proved the didactic and tourist relevance of geosites and geodiversity sites. Attractions were classified as nationally relevant in the criteria, with values ​​varying between 310 and 380 points in didactic value and between 245 and 400 in tourist value. In terms of scientific value, good results were also found, varying between 135 and 330 points, with attractions of local and national relevance and two with international prominence, scoring above 300 points.